Efek Moderasi WOM Pada Pengaruh Fasilitas Dan Lokasi Terhadap Proses Pengambilan Keputusan - Cecilia Eka Erratna B; Endang Tjahjaningsih (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Before deciding to rent, some prospective clients must first seek information about the Vina House building through colleagues or family or anyone who has rented the building, how the packages are in it, how the facilities are obtained. The results of previous research conducted by Kurniawan (2015) are that facilities and location have a positive and significant effect on purchasing decisions, while Memah et al., (2015) give the results that facilities have a positive but not significant effect on consumer purchasing decisions. Furthermore, Latief (2018) provides research results that the location variable has no significant effect on consumer buying interest. Referring to the phenomena and gaps in research results, this study aims to determine the moderating effect of WOM on facilities and locations on the rental decision-making process. Based on the research objectives to be achieved, the type of research used by the researcher is explanatory research. The results of further calculations show that the regression coefficient value of the word of mouth variable as a moderator has a regression value of -0.015 which is negative with a calculated significance value of 0.085 > 0.1. The value of the regression coefficient of the word of mouth variable as a moderator has a regression value of -0.050 which is negative with a calculated significance value of 0.007 <0.1.